Tropomyosin receptor kinase inhibitors: a patent update 2009 – 2013. (July 2014) - McCarthy, Clive; Walker, Edward
<x xml:space="preserve">Abstract</x> Introduction: Tropomyosin receptor kinases (Trks) are a family of three similar tyrosine kinases activated by peptide hormones of the neurotrophin family. The nerve growth factor antibody tanezumab has provided clinical proof of concept for inhibition of the TrkA pathway in pain. As an alternative modality, small-molecule inhibitors of the Trks have been pursued in recent years to probe the role of these neurotrophin pathways in pain, cancer and other indications. Areas covered: This paper reviews the patent literature between mid-2009 and 2013, claiming inhibitors of Trk family members as the primary biological targets. Additional patents have been reviewed where Trk is not the main kinase of interest but in which high Trk potency is observed and the chemical matter is particularly noteworthy. Patents pre-dating this period have been reviewed previously. Scifinder and Google were used to find relevant patents and clinical information using Trk or Tropomyosin as the search term. Expert opinion: Considerable recent progress has been made in the identification of selective pan Trk inhibitors with pharmacodynamic and pharmacokinetic properties appropriate for clinical evaluation. Inhibitors of both active and inactive conformations of the Trks as well as peripherally restricted molecules have been identified. Furthermore, TrkA-selective allosteric inhibitors have recently been disclosed, which enables the biology of this isoform to be probed. The recent identification of a TrkA gene fusion in a subset of lung cancer patients will increase further the attraction of Trk inhibition to the pharmaceutical industry.